(untitled) (Entrepreneurship Journal for Finance and Business, 2023)
The research aims to show the role of resource consumption accounting in the process of rationalizing the distribution of costs of productive service centers in economic units as one of the most important approach that help to provide relevant information on how to optimize the exploitation of resources and corresponding activities which leads to increasing the efficiency and effectiveness of performance as a result of reducing costs, which is reflected in the increase in profits, as well as showing the volume of unemployed energy and working to employ it through the production of useful costly information that helps it face developments in the business environmentThis is reflected in the rationalization of decisions made by economic units. The problem is that the methods used in the distribution of the costs of production service centers by local units suffer from shortcomings in this area because they rely on traditional methods in the distribution of the costs of these centers, which results in distortion in the information provided to determine the cost of products.This led to its failure to provide information that helps management make decisions and that using RCA helps economic units keep pace with developments in the business environment. Assists them in making and making decisions that are in the company’s interest, such as a resource consumption accounting system that focuses on providing reliable information to rationalize costs and maximize revenues to enhance the company’s productive capacity. For the company where it aims to achieve greater success in the competition market, as well as it is based on resources, and is focused on them instead of activities and includes resources in accounting for the consumption of resources consumed by activities only, but includes resources consumed by the resources themselves. In light of these conclusions, a set of recommendations was reached, the most important of which is to help the application of modern management accounting systems that keep pace with the developments of the business environment and provide adequate and appropriate information to economic units.Keywords: accounting for resource consumption, exploitation of idle energy, cost reduction.